Mobile Game for Equality of Fractions for Elementary School Students - Wulandari, Ayu; Amir, Mohammad Faizal (International Journal of Elementary Education, 2021)
The low learning outcomes in the equality of fractions material are due to the unavailability of mobile technology game media that can train and explore the pattern of equality of fractions appropriately. This study aims to produce a valid, practical, and effective mobile game for equality of fractions (MoGEF) to improve learning outcomes on equality of fractions material. This study uses research and development methods through analysis, design, development, implementation, and evaluation. The subjects of this study were 29 students in the fourth grade of elementary school. Validity was measured by assessing two experts (mathematical education expert and information technology education expert). Practicality was measured through the results of the student response questionnaire, while effectiveness was measured through the posttest of student learning outcomes after using MoGEF. Data were collected using questionnaires and tests. The validity results obtained an average of 86.06% in the interval of 85.00% 100.00% with completely valid criteria. Practicality obtained an average of 4.659, which is in the interval of 2.50  3.25 with very practical criteria. Effectivenes shows the criteria of 79.83% berada pada interval 70.00%  85.00% dengan kriteria efektif. The effectiveness of the mobile game obtained a significance value of 2.127 > 2.048, which means it can improve the learning outcomes of elementary school students in the equality of fractions material. Therefore, the development of mobile games for equality of fraction is concluded to be very valid, very practical, and effective.